Penentuan Kadar Residu Pestisida Klorpirifos dan Pengaruh Pencucian pada Cabai, Buncis dan Sawi Putih serta Nilai Risiko Kesehatan pada Manusia - Zilfa Zilfa; Yulizar Yusuf; Mitha Anggreini Putri; Fheiza Heysha (Inovasi Kesehatan Global, 2026)
Vegetables are food commodities widely consumed by the public due to their high nutritional content. Chili (Capsicum annuum L.), green beans (Phaseolus vulgaris L.), and Chinese cabbage (Brassica pekinensia L.) are among the vegetables that can be processed into various delicious dishes or consumed fresh as raw vegetables. To obtain healthy and high-quality vegetable crops, pesticides are commonly used to control pests that may damage the plants. One of the widely used pesticides is chlorpyrifos, which can leave residues that may pose both acute and chronic health risks. Therefore, it is necessary to analyze the levels of chlorpyrifos pesticide residues in vegetables. The residue levels were determined using a UV-Vis spectrophotometer at a wavelength of 230 nm with dichloromethane as the solvent, while qualitative analysis was performed using HPLC by comparing the retention times of standard solutions and vegetable samples. In this study, washing treatments were applied to the vegetables using dichloromethane, distilled water, well water, and tap water (PDAM) to evaluate the effect of washing on pesticide residue levels. The concentrations of pesticide residues in unwashed vegetables were chili (2.6680 ± 0.0214 mg/kg), green beans (2.4658 ± 0.0193 mg/kg), and Chinese cabbage (2.7950 ± 0.0379 mg/kg). The washing process was carried out three times for each solvent. After three washings using dichloromethane and distilled water, pesticide residues were no longer detected, whereas washing with tap water (PDAM) and well water still left residues, although at levels much lower than the Maximum Residue Limit (MRL). The health risk assessment showed that the aHQ and cHQ values were < 1, indicating that consumption within the recommended limits of these samples does not pose health risks, either in the short term or long term. This study provides important information that repeated washing is necessary to effectively reduce pesticide residue levels in vegetables before consumption.